The Relationship Between PolyAI Usage Patterns and Students Success In English Subject At A Senior High School - Rizky, Zafira Alia; Halim*, Abdul (Universitas Syiah Kuala, 2024)
With the increasing use of Artificial Intelligence (AI), we need ti be able to use and deploy it as effectively as possible to avoid misuse. A chatbot is an AI system that simulates human conversation. If used correctly, chatbots could be integrated into the field of education. This study investigated the use and implementation of the PloyAI chatbot to improve the English learning of students in MAN 1 Samarinda. The purpose of the study was to investigate how high school students could be used to further the use of PolyAI in education field. The aim was to provice new perspectives that would enchane the current discussion on the integration of artificial intelligence in education. This study used a quantitative approach with questionnaires and English tests as research tools. The data obtained were analyzed using Statistical package for the Social Sciences (SPSS) to discover the relationship between two variables. The results of the study show that the implementation of PolyAI has improved the perfomance of students in English courses.